KINERJA BADAN KEPEGAWAIAN DAERAH DALAM MENYELENGGARAKAN DIKLAT APARATUR SIPIL NEGARA DI PEMERINTAH KOTA TOMOHON - TAMON, VILLA SATRIA PUTRI; LENGKONG, fLORENCE DAICY; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrack : In Government Regulation Number 101 Year 2000 on Education and Training of Civil ServantsPosition stated that the training is the process of organizing learning in order to improve the ability of theCivil Service / Administrative Civil State. The third term (education, training, development) are related toeach other and sometimes complementary. This research was conducted at the Regional Employment BoardTomohon, in particular education and training. Implementation of Education and Training (Training) in theState Civil Apparatus Tomohon City Government is one of the government's efforts to improve the quality ofASN in terms of national awareness, personality and ethics of the State Civil Apparatus.This research was conducted in order to determine how the performance of Regional Employment Agency inorganizing the State Civil Training Apparatus in Tomohon City Government. The research was conductedusing qualitative methods, with 10 informants. The study was conducted with technical documentation study,observation and interviews and data analysis Miles and Haberman model analysis, namely data reduction,data presentation and conclusion.The results showed: Performance of Tomohon City Regional Employment Board in organizing theASN Training has been good enough because it is supported by the implementation of a training programthat is running well; the quality of human resources personnel a good employee and organizational support.Factors inhibiting the performance of BKD organizing ASN Training in Tomohon is a factor supportinginfrastructures are not yet supporting and budget and employee discipline. While supporting factor is thesupport organization, partnerships, human resource personnel with adequate and continuous training. Theeffort that has been done is to include in the future work program constraints and needs required by BKDforward in the vision, mission, goals and objectives of the organization, in the form of provision of trainingfacilities and infrastructure such as buildings and dormitories training; improving the quality and capacity ofthe resource; improve discipline and performance of civil servants; improve the well-being and improve thecoordination / consultation of personnel affairs.Keywords: Education; training; BKD performance.